Излучатель повышенной спектральной яркости для передатчика резонансного лидара - Басецкий, В. Л.; Зарудный, А. А. (ХНУРЭ, 2011)
The spatially-angular and power characteristics of the dye laser with lamp pump are presented. The theoretical and experimental researches, directed to the spectral power radiance advancement are performed. The results of examinations were used for the development of transmitters functioning in a composition of resonance lidar stations.
Keywords: коэффициент отражения выходного зеркала резонатора; спектральная резкость